My favorite universe - Tyson, Neil deGrasse; Teaching Company (Chantilly, VA : Teaching Co., 2003)
Clear introductions to essential principles of physics support these lectures, including density, quantum theory, gravity, and the General Theory of Relativity. Also includes forays into disciplines such as chemistry and biology as needed to explain events in astronomy.
lecture 1. On being round -- lecture 2. On being rarefied -- lecture 3. On being dense -- lecture 4. Death by black hole -- lecture 5. Ends of the world -- lecture 6. Coming attractions -- lecture 7. Onward to the edge -- lecture 8. In defense of the big bang -- lecture 9. The greatest story ever told -- lecture 10. Forged in the stars -- lecture 11. The search for planets -- lecture 12. The search for life in the universe.
DVD, region 1.
Lectures by Professor Neil deGrasse Tyson based on essays written by him for Natural History magazine.
Course guidebook includes bibliography.
Keywords: Astrophysics -- Popular works; Cosmology -- Popular works; Educational films